Motivasi Mahasiswa Program A (Jalur Ujian Masuk Perguruan Tinggi Negeri) Melanjutkan Studi di Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Gadjah Mada Yogyakarta - Ibrahim Rahmat, M. Djumarin, Dri Atmak (Berita Kedokteran Masyarakat (BKM), 2003)
Background: Nursing Study Program as a new program in Faculty of Medicine Gadjah Mada University opens 2 admission program which are program A and program B. Program A for students graduated from senior high school and program B for students graduated from Nursing Academy. This study only explores for program A because the students do not understand yet about nursing before, thut we can understand inside motivation of the students.Purpose: This study was done to explore factors that motivate students both instrinsic and extrinsic motivation. Instrinsic motivations such as to improve knowledge and to get a job. Extrinsic motivations such as suggestion from others, self esteem and acknowledgement motivation.Method: The method from this study is explorative descriptive. The number of respon-dent is 109 respondents consist of 57 Program A students in semester 2 and 52 pro-gram A students in semester 4. Data collection used a close questionnaire which has been tried before with the validity level of 0.303 – 0.826 and the reliability level of 0.93. Result and Conclusion: Result of this study showed that 1) majority of respondents agreed that their motivation is to improve their knowledge; 2) only half of respondents agreed that their motivation is to get a job; 3) only a small number of respondents agreed that their motivation are to follow the suggestion from others and to have achieve-ment from people.Conclusions the vast majority of the motivation are improve their knowledge and to get a job, and only small number of the studens are to follow the suggestion from others, self esteem and acknowledgement motivation. For recommen-dation that students who have a good motivation should be maintained motivations and for students who have extrinsic motivation should be improve by developing instrinsic motivation. Keywords: Motivation-Nursing Study Program